Shortwave Ultraviolet Persistent Luminescence of Sr2MgSi2O7: Pr3+ - Antuzevics, Andris; Doke, Guna; Krieke, Guna; Rodionovs, Pavels; Nilova, Dace; Cirulis, Jekabs; Fedotovs, Andris; Rogulis, Uldis (MDPI, 2023)
Currently, extensive research activities are devoted to developing persistent phosphors which extend beyond the visible range. In some emerging applications, long-lasting emission of high-energy photons is required; however, suitable materials for the shortwave ultraviolet (UV–C) band are extremely limited. This study reports a novel Sr2MgSi2O7 phosphor doped with Pr3+ ions, which exhibits UV–C persistent luminescence with maximum intensity at 243 nm. The solubility of Pr3+ in the matrix is analysed by X-ray diffraction (XRD) and optimal activator concentration is determined. Optical and structural properties are characterised by photoluminescence (PL), thermally stimulated luminescence (TSL) and electron paramagnetic resonance (EPR) spectroscopy techniques. The obtained results expand the class of UV–C persistent phosphors and provide novel insights into the mechanisms of persistent luminescence. © 2023 by the authors.--//-- This is an open access article Antuzevics A., Doke G., Krieke G., Rodionovs P., Nilova D., Cirulis J., Fedotovs A., Rogulis U.; Shortwave Ultraviolet Persistent Luminescence of Sr2MgSi2O7: Pr3+ (2023) Materials, 16 (5), art. no. 1776; DOI: 10.3390/ma16051776; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85149833044&doi=10.3390%2fma16051776&partnerID=40&md5=03c546fb3fc6c7d6c16d4d482b4038ca published under the CC BY 4.0 licence.
This research is funded by the Latvian Council of Science, project “Defect engineering of novel UV–C persistent phosphor materials”, Project no. lzp-2021/1-0118. Institute of Solid State Physics, University of Latvia, as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; afterglow; electron spin resonance (ESR); long-lasting luminescence; melilite; thermostimulated luminescence (TSL); UVC